PARADIGMA KEMANUSIAAN DALAM PENDIDIKAN ISLAM - M. Yemmardotillah (El-Rusyd, 2019)
The ideal man is a perfect human being. That appears and in line with the apostolic mission of Prophet Muhammad SAW, that is to perfect the noble character. Islam is a universal religion that teaches mankind about various aspects of life both worldly and enduring. The purpose of this discussion is to know how the humanitarian paradigm in Islamic education, Humanistic education seeks to develop the individual as a whole through real learning. The development of emotional, social, mental, spiritual and skill-related aspects of a career becomes the focus of the humanistic education model. The results show that Islamic education will develop human (learners) on all aspects and power that exist in self and environment in a balanced and integrated without prioritizing and exaggerating one of the elements that have an impact on reducing the other elements. Islamic education is not an education that only refers to ukhrawi life and not education which only focus on worldly interests, but Islamic education oriented to a balanced life between worship and muamalah, between the world and the hereafter, besides Islamic education also try to develop aspects society as a cultural symbol in the form of affection, respecting respect for each other as long as it is not contrary to the religious.